Pattern of Renal Diseases in Children Presented to King Abdulaziz University Hospital - Hussain M. Alsaggaf (Journal of King Abdulaziz University: Medical Sciences, 2023)
The pattern of renal diseases in children presented to the tertiary pediatric nephrology center at King Abdulaziz University Hospital was reviewed respectively over the period of 8 years (20052012). A total of 850 children were seen. Male: female ratio is 2:1. Median (range) age at presentation was 9 (0.01-16) years. Fifty-five percent were Saudi and 45% were from various nationalities. Underlying etiology was congenital or inherited disease in 55.5% of the children. Glomerular diseases were the most common in acquired causes while obstructive uropathy was the most common in congenital causes. Non-neurogenic neurogenic bladder was the most common underlying diagnosis of children with urological abnormalities (28%), followed by posterior urethral valve (26%). Nephrotic syndrome was the most common of glomerular diseases with 31% with steroid resistant nephrotic syndrome. Renal impairment was present in 315 children with low glomerular filtration rate; chronic kidney disease stage 2 in 88, stage 3 in 84, stage 4 in 35 and stage 5 in 108. In conclusion, childhood congenital or inherited renal diseases were the majority. Non-neurogenic neurogenic bladder was the most common urological abnormality and nephrotic syndrome was the most common glomerular disease with high percentage of steroid resistant nephrotic syndrome. A considerable percentage presented with advanced chronic kidney disease.